(3Yjhf GdQhVJjf aj CNHGQ GdOhdJjfs - (3YHO GdQMef Hf ESeGYjd Hf EHQGgje GdebOSj GdOeTbqj, CHh GdbGSe, TgGH GdOjf, CHh TGeI,J (B665 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO agPG eNJUQ cJGH GdQhVJjf GdfhQjI hGdUdGMjI GdPi Ufag GdYdGeI TgGH GdOjf GdeYQha HCHi TGeI s
(3BNQgG (B:s
(3jfJgi HJQLeI GdbGVi GdaGVd Hbhdg (B: (3hPcQ LeGYI ef GdOjGQ GdeUQjI Cfg Nda ef GdcJH ebOGQ eGFI Cda eLdO hcGf jLeYgG ef SGFQ GdHdGO QMeg Gddg Ydjg BNQ GdeNJUQ s
(3HgG fXGe GdJYbjHIs
(3YdjgG JedcGJ hbQGAGJs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B125s
Keywords: (3GdJGQjNs